Vertebral Artery Loops and Cervicobrachial Pain - Nichanametla Sravani; Krishnan Nagarajan; Manchikanti Venkatesh; Veer S. Negi; Andi S. Ramesh (Indian Journal of Neurosurgery)
Vertebral artery loop formation is an uncommon anatomical variation which may be asymptomatic or can cause cervicobrachial pain, radiculopathy, or even bone erosions and enlargement of neural foramina. As this entity is one of the uncommon causes of cervical radiculopathy, this report aims to create awareness among radiologists and clinicians, as vertebral artery loops may be seen incidentally in routine neuroimaging. magnetic resonance imaging (MRI) with magnetic resonance (MR) angiography or multislice computerized tomography (CT) angiography plays an important role in diagnosing as well as creating a roadmap for the surgery. Vertebral artery loop formation as a cause of radiculopathy is an uncommon condition. An abnormal course of vessel can lead to vascular injury during surgery, hence preoperative evaluation with CT or MRI is essential.1 2 Anomalous looping of vertebral artery can cause neurovascular compression apart from bony erosion, widening of vertebral foramen, and even vertebrobasilar insufficiency. Clinical features of vertebral artery loop formation can be radiculopathy, compression over cervical cord leading to sensory and motor deficit, and vertigo when associated with vertebra–basilar insufficiency, which is known as vascular vertigo. It has also been postulated that loop formation of vertebral artery can also lead to posterior circulation infarcts. Left vertebral artery is more prone for loop formation than the right vertebral artery, probably due to increased caliber in greater proportion of individuals. Multilevel and bilateral tortuosity can occur in younger patients rarely where imaging plays an important role.